2004
DOI: 10.1590/s0021-75572004000200007
|View full text |Cite
|
Sign up to set email alerts
|

Resposta imune à vacinação contra hepatite B em recém-nascidos pré-termo, iniciada no primeiro dia de vida

Abstract: Objective: To investigate the immune response of preterm infants to hepatitis B vaccination.Methods: Three doses of recombinant hepatitis B vaccine (5 µg dose) were administered to 35 preterm and 21 full-term infants within 24 hours after birth and at one and six months of postnatal age.Results: A protective antibody response (anti-HB > 10 mUI/mL) was observed three months after the last dose in 92.6% and 100% of preterm and full-term infants (p > 0.05), respectively. Newborns with gestational age below 34 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
0
8
0
9
Order By: Relevance
“…6,54 In premature newborns, weighing less than 2 kg, the antibody levels are lower and the seroconversion rates smaller. A recent study conducted by Sadeck & Ramos, 56 about response to vaccination in pre-term newborns, showed a similar response to that in full term babies. However, in 25% of those with birthweight equal to or lower than 1,500 g, the response was not satisfactory.…”
Section: Hepatitis B Vaccinementioning
confidence: 58%
See 1 more Smart Citation
“…6,54 In premature newborns, weighing less than 2 kg, the antibody levels are lower and the seroconversion rates smaller. A recent study conducted by Sadeck & Ramos, 56 about response to vaccination in pre-term newborns, showed a similar response to that in full term babies. However, in 25% of those with birthweight equal to or lower than 1,500 g, the response was not satisfactory.…”
Section: Hepatitis B Vaccinementioning
confidence: 58%
“…The authors indicated the need to assess seroprotection after the third dose of the vaccine or administer 1 booster dose at 12 months. 56 Among adolescents and adults, the antibody response rates are 20% to 30% after one dose, 75% to 80%…”
Section: Hepatitis B Vaccinementioning
confidence: 99%
“…Crianças com peso ao nascer acima de 2 kg respondem de forma semelhante às de termo e de peso adequado 7,43 . A vacinação a partir de 1 mês de idade já apresenta resposta adequada, independendo do peso de nascimento, o que autoriza o início da vacinação aos 2 meses de idade, com qualquer peso, e a partir de 1 mês de idade em prematuros clinicamente estáveis na alta hospitalar 6,7,43 .…”
Section: Imunização Ativaunclassified
“…In general, these studies included NB from a wide gestational age and birth-weight range, with the majority of the members of the sample groups having gestational ages close to 36 weeks or birth weights close to 2,000 g. 5,6 In contrast, other studies that have performed early vaccination on larger numbers of preterm NB whose birth weights were < 1,500 g or gestational ages < 32 weeks, 2,3,7-9 including a study we performed of Brazilian children, 10 have identified significantly lower levels of immunogenicity among preterm NB after the complete course of vaccination was completed (60-77%) than among full term NB (98-100%). While the study made by Sadeck & Ramos was not designed for this end, it too identified a reduced frequency of post-vaccination protective antibody levels within the subgroup of preterm NB born weighing less than 1,500 g. 4 What are the implications of reduced vaccination immunogenicity among preterm NB born at less than < 1,500-1,800 g and/or with a gestational age < 32-34 weeks for infant VHB infection prevention?…”
Section: See Related Article On Page 113mentioning
confidence: 99%
“…4 The two groups were compared b y means of testing for protective anti-HBs antibody levels (> 10 mUI/ml) before the third vaccine dose, at 9 months and at 12 months. Despite identifying a tendency, before the third dose was given, towards a lower frequency of protective antibody levels among preterm children, due to a reduced response to the first two doses from those whose gestational age < 34 weeks and/or, and more…”
mentioning
confidence: 99%